Increment of Material Properties of EN24 Pinion by Heat Treatment Process - Tamilarasu, P.; Praveen, J. Jones; Siddharthan, B.; Vivek, U.; Giridharan, M. (Advanced Aspects of Engineering Research Vol. 13, 2021)
This study aimed to determined the enhancement of material properties of EN24 pinion by heat treatment process. The process of heat treatment is carried out by heating the base material above critical temperature and then cooling with salt water, air and oil. The failure analysis was carried out on a failed pinion gear which is used for power transmission system in the automobile sector. The pinion gear is made of case carburized steel with low nickel and chromium content and it also has undergone extensive corrosion due to an environmental problem. The teeth are badly damaged and corroded at the surface. However, the crack has occurred due to stress and it is found only in certain places. To improve the corrosion resistance, nickel and chromium content are added and also heat treatment is carried out. The mechanical properties and wear resistance are improved in EN24 steel when compared to failure gear and EN24 steel before heat treatment.